Development of blast-resistant rice variety derived from crossing between MR219 and Pongsu Seribu 1 through marker-assisted selection - Miah, Gous (2015)
Marker-assisted selection (MAS) is very effective and powerful method for efficient selection of the target gene. MAS can potentially accelerate breeding programs for varietal resistance. Marker-assisted backcrossing (MABC) is the most-effective way of transferring specific gene(s) to an agronomically superior variety. Rice blast disease, caused by the fungus Magnaporthe oryza, is one of the most devastating and destructive disease causing significant yield loss worldwide as well as Malaysia. The most-effective approach to preventing this disease is the genetic improvement using resistant varieties. In this study, blast resistance gene (putative Piz) was transferred from an indica rice donor Pongsu Seribu 1, using MABC method, into a blast susceptible elite indica rice variety, MR219. Therefore, a cross between rice variety MR219 and Pongsu Seribu 1 was performed to incorporate blast resistance gene(s) into MR219 variety without losing their quality. Sixteen microsatellite markers tightly linked to the blast resistant genes were selected and used in this study to determine potential association with blast resistance gene. These polymorphic foreground markers were used for confirmation of blast resistant genes in F1 population. After that only two microsatellite markers, RM6836 and RM8225, that conferred blast resistance gene (putative Piz) located on chromosome 6 were used to BC1F1, BC2F1 and BC2F2 populations related to resistance against the most-virulent Malaysian rice blast pathotype P7.2 of Magnaporthe oryzae. Out of 375-microsatellite markers, 70 markers were found to have polymorphism between the parental lines and were used for background analysis in each generation. The inheritance of the resistance gene against the pathotype P7.2 was investigated on BC2F1 and BC2F2 populations. The parent MR219 showed susceptible reaction with lesion score 5 to 7, whereas Pongsu Seribu 1 was found as resistant producing lesion score 0 to 2 after exposing to P7.2 inoculum in the glasshouse. In BC2F1 population, 333 plants were challenged with pathotype P7.2. Among them, 159 plants showed resistant reaction and another 174 plants showed susceptible reaction to blast. The observed frequencies were tested for goodness of fit with chi-square (χ2) test for single dominant gene model. The goodness of fit (p=0.4463) to the expected test cross ratio (1:1) showed that the resistance is controlled by a single nuclear gene. The plants resistant to blast pathotype P7.2 from BC2F1 population showed good fit with two markers, RM6836 (χ2=0.20; p=0.6547) and RM8225 (χ2=1.20; p=0.2733) with expected test cross ratio (1:1) for single gene model. These two markers were found suitable for marker-assisted selection conferring blast resistance gene against the pathotype P7.2. The phenotypic reaction on the blast incidence of BC2F2 population segregated in 3:1 ratio (resistance to susceptible). The genotypic segregation of BC2F2 population using RM6836 and RM8225 markers showed 1:2:1 ratio. Results confirmed that single dominant gene governs blast resistance in Pongsu Seribu 1 variety. The background analysis of the improved lines indicated recurrent parent genome recovery ranging from 75.40 % to 91.30 % in BC1F1, 80.40% to 96.70% in BC2F1 and 92.7% to 97.7% in BC2F2 generation. The average proportion of the recurrent parent in BC2F2 selected improved lines was 95.98%, explaining the very close similarity at phenotypic level with the parental variety, MR219. Thirteen homozygous plants consist of blast resistant gene which is phenotypically similar with MR219 backgrounds were selected as an improved blast resistant breeding lines. The agronomic characters showed no significant difference between MR219-parent and blast resistant MR219 improved lines. The improved lines possessing blast resistant gene (putative Piz) with desirable agronomic traits that can be used as a valuable source for further blast resistance rice breeding programs. In conclusion, from this research rice blast resistance in Pongsu Seribu 1 is governed by a single dominant gene located on chromosome 6, which is linked to RM6836 and RM8225 markers. This information could be used in MAS for blast resistance in other rice crosses involving Pongsu Seribu 1.